1986
DOI: 10.1210/endo-118-3-980
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cytosolic Free Ca2+Concentrations in Human and Rat Osteosarcoma Cells: Actions of Bone Resorption-Stimulating Hormones*

Abstract: Influx of extracellular Ca++ into bone cells has been postulated as an early action of PTH and other bone resorption-stimulating factors. To test this hypothesis directly, we measured the cytosolic free Ca2+ concentration ([Ca2+]i) in two hormone-responsive human (SaOS-2 and G-292) and two rat osteosarcoma cell lines (Ros 25/1 and Ros 17/2.8) and in primary cultures of bone cells from neonatal mouse calvaria using the fluorescent Ca2+ indicator Quin 2. Actions of bovine PTH-(1-34), vasoactive intestinal peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

1986
1986
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 31 publications
3
37
0
2
Order By: Relevance
“…This is in contradiction to Kaplan et al (17) who reported that PTH did induce a small [Ca 2ϩ ] i elevation. Earlier studies also confirm that the effect of PTH on [Ca 2ϩ ] i mobilization in osteoblasts is controversial, one group finding no effect (24), but others reporting various increases (25,26). A possible explanation for these very different reports may be the presence of ATP in the culture medium due to cell lysis.…”
Section: Discussionmentioning
confidence: 84%
“…This is in contradiction to Kaplan et al (17) who reported that PTH did induce a small [Ca 2ϩ ] i elevation. Earlier studies also confirm that the effect of PTH on [Ca 2ϩ ] i mobilization in osteoblasts is controversial, one group finding no effect (24), but others reporting various increases (25,26). A possible explanation for these very different reports may be the presence of ATP in the culture medium due to cell lysis.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies on SaOS-2 cells reported that PTH did not stimulate acute increases in [Ca 2ϩ ] i (33). However, PTH has been shown to elicit transient increases in [Ca 2ϩ ] i and generate inositol polyphosphates in other osteoblast-like cell lines (4,5,15); therefore, we examined the role of the inositol lipid/Ca 2ϩ / PKC signaling pathway in the stimulation of ECAR by PTH.…”
Section: Role Of Na ϩ /H ϩ Exchange In the Pth-induced Increase In Ecar-mentioning
confidence: 94%
“…A minimum of five consecutive data points from the base-line ECAR of each cell population were selected and averaged, and then all other data points were expressed as a percentage of this basal average. (32,33). In brief, the cells in the monolayer were detached from the culture dish using Ca 2ϩ -free Hanks' balanced salt solution (HBSS) consisting of 120 mM NaCl, 4 mM KCl, 10 mM D-glucose, and 20 mM HEPES, pH 7.2, supplemented with 5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cDNA probably represents ALP of bone origin since it was derived from Saos-2 osteosarcoma cells that have osteoblastic properties (7). Partial amino acid sequences obtained from purified liver ALP are identical to portions of the polypeptide encoded by the L/B/K cDNA.…”
mentioning
confidence: 99%